A systematic review of the effect of therapists’ internalised models of relationships on the quality of the therapeutic relationship - Steel, C.; Macdonald, J.; Schröder, Thomas (Wiley, 2018)
The quality of the therapeutic relationship has been identified as a key factor in predicting client outcomes, accounting for around 8% of variation (Horvath, Del Re, Flückiger, & Symonds, 2011; Martin, Garske, & Davis, 2000; Wampold, 2001). Although therapist factors have been seen as less relevant to therapeutic relationship quality than client factors, focus on therapist factors has steadily increased in line with the view that the therapist responds differently to different clients, due to their own personal characteristics and unconscious processes. Relational theory suggests that the therapist’s particular qualities combine with the client’s particular qualities to form a unique interpersonal context (e.g. Wachtel, 2008). Safran and Muran (2000) suggest that the interpersonal context is heavily influenced by client and therapist internalised patterns of relating formed in early childhood. Evidence shows that certain therapist factors do affect therapeutic relationship quality; the qualities of dependability, warmth and responsiveness in therapists have all been found to create stronger alliances (Ackerman & Hilsenroth, 2003). The importance of these mostly interpersonal characteristics imply that the internalised relational models of therapists may also be important in determining the type of relationship that is built and the therapeutic processes occurring within.